How career expectations influence advancement: evidence from women in the hospitality industry. Issue 6 (4th September 2020) - Liu, Ting; Gao, Jie; Zhu, Mingfang; Qiu, Yajun
Abstract : Purpose: This study aims to examine the role of women's career expectations (CEs) in changes in their career advancement (CA) and to determine whether these changes were because of socio-demographic factors. Design/methodology/approach: Multiple linear regression was used to measure the relationship between women's CEs and CA, as well as the influences that socio-demographic factors (e.g. education) have on that relationship. Findings: Results indicated that CEs had two dimensions (i.e. career rewards and career development) and that career reward expectations had a significantly higher effect on CA than career development expectations. Furthermore, women were very likely to set higher CEs and stronger desires for CA as they became older. Results also showed that education, working years and position level were significantly related to women's CA. Practical implications: This study provides new insight into which aspects of women's CA can be boosted by CEs and how these aspects may be affected by socio-demographic factors. This study can help hotels design better career management strategies to achieve the desired results. The study also provides guidance for women's career management activities. Originality/value: This study considers women's CEs in hotels. The results revealed two dimensions (i.e. career rewards and career development) of CEs and uncovered the influences of socio-demographic factors on women's CA, for example, age, education, working years and position level. Abstract : 职业期望如何影响职业晋升？——来自酒店业女性员工的证据 摘要 研究目的: 基于对酒店业两个变量（即职业期望和职业晋升）的理解, 本研究旨在考察职业期望在妇女职业晋升变化中的作用, 并确定这些变化是否由社会人口特征因素引起。 设计/方法/途径: 采用问卷调查的方式收集数据。采用多元线性回归来衡量女性职业期望和职业晋升之间的关系, 以及社会人口特征因素（如教育）对这种关系的影响。 研究结果: 结果表明, 职业期望有两个维度（即职业奖励和职业发展）, 职业奖励期望对职业晋升的影响明显高于职业发展期望。此外, 随着年龄的增长, 女性倾向于有更高的职业期望和更强烈的职业晋升愿望。结果还显示, 受教育程度、工作年限、职位级别与女性的职业晋升显著相关。 实践意义: 这项研究为女性职业期望在哪些方面可以促进职业发展以及社会人口特征因素如何影响这些方面受到的提供了新的见解。这项研究可以帮助酒店设计更好的职业管理策略, 以达到预期效果。本研究也为女性的职业管理活动提供了指导。 原创性/价值: 本研究将职业期望引入酒店业中女性员工职业发展研究。结果显示职业期望的两个维度（即职业奖励和职业发展）, 并揭示了社会人口学因素如年龄、学历、工作年限和职位级别等对女性职业晋升发展的影响, 。 Abstract : Cómo las expectativas profesionales influyen en el avance: Evidencia de las mujeres en la industria hotelera Resumen Propósito: basado en la comprensión de dos variables (es decir, expectativas profesionales y avance profesional) en la industria hotelera, este estudio tuvo como objetivo examinar el papel de las expectativas profesionales en los cambios en el avance profesional de las mujeres y determinar si estos cambios se debieron a factores sociodemográficos. Diseño/metodología/enfoque: Se Utilizó Un Cuestionario Para Recopilar Datos. Se Utilizó La Regresión Lineal Múltiple Para Medir La Relación Entre Las Expectativas Profesionales De Las Mujeres Y El Avance Profesional, Así Como Las Influencias Que Los Factores Sociodemográficos (Por Ejemplo, La Educación) Tienen En Esa Relación. Resultados: Los Resultados Indicaron Que Las Expectativas De Carrera Tenían Dos Dimensiones (Es Decir, Recompensas De Carrera Y Desarrollo De Carrera) Y Que Las Expectativas De Recompensa De Carrera Tenían Un Efecto Significativamente Mayor En El Avance De La Carrera Que Las Expectativas De Desarrollo De Carrera. Además, Las Mujeres Tenían Más Probabilidades De Tener Expectativas Profesionales Más Altas Y Deseos Más Fuertes Para Avanzar En Su Carrera A Medida Que Envejecían. Los Resultados También Mostraron Que La Educación, Los Años De Trabajo Y El Nivel De Posición Estaban Significativamente Relacionados Con El Avance Profesional De Las Mujeres. Implicaciones prácticas: Este Estudio Proporciona Una Nueva Perspectiva Sobre Qué Aspectos Del Avance Profesional De Las Mujeres Pueden Ser Impulsados Por Las Expectativas Profesionales Y Cómo Estos Aspectos Pueden Verse Afectados Por Factores Sociodemográficos. Este Estudio Puede Ayudar A Los Hoteles A Diseñar Mejores Estrategias De Gestión Profesional Para Lograr Los Resultados Deseados. El Estudio También Proporciona Orientación Para Las Actividades De Gestión Profesional De Las Mujeres. Originalidad/Valor: este estudio considera las expectativas profesionales de las mujeres en la industria hotelera. Los resultados revelaron dos dimensiones (es decir, recompensas profesionales y desarrollo profesional) de las expectativas profesionales y descubrieron las influencias de los factores sociodemográficos en el avance profesional de las mujeres, por ejemplo, edad, educación, años de trabajo y nivel de posición.